Healthcare Resource Utilization and Cost Comparisons of High-Protein Enteral Nutrition Formulas Used in Critically Ill Patients - Matthew C. Bozeman; Laura L. Schott; Amarsinh M. Desai; Mary K. Miranowski; Dorothy L. Baumer; Cynthia C. Lowen; Zhun Cao; Krysmaru Araujo Torres (Journal of Health Economics and Outcomes Research)
# Background High-protein enteral nutrition is advised for patients who are critically ill. Options include immunonutrition formulas of various compositions and standard high-protein formulas (StdHP). Additional research is needed on the health economic value of immunonutrition in a broad cohort of severely ill hospitalized patients.